Niche separation between Encarsia dispersa and Encarsia guadeloupae, two biological control agents of the spiraling whitefly Aleurodicus dispersus, in Benin, West Africa - Obinna, A.; Peter, N.; Korie, S. (Springer, 2011)
The spiraling whiteflyAleurodicus dis-persus(Russell) is an insect pest that causessubstantial damage to ornamental plants, shade treesand food crops. It was first observed in Benin in 1993.Two host specific parasitoids,Encarsia dispersaandE. guadeloupae,fortuitously introduced with its host,were recovered in the second half of 1993 inSouthern Benin. Survey results from 1993 to 1995(already published) showed the decline in the popu-lation ofA. dispersusdue to the parasitoids, and thespread from Cotonou (6°100N) in a northern direc-tions of both parasitoids and their host. Results fromsimilar field surveys from 1996 to 2003 documentthat the spiraling whitefly and both its parasitoidsspread to Natitingou (10°200N, 540 km) in 1995 andBembereke (10°140N) in 1996, wherebyE. dispersaarrived within less than a year of its host and quicklybecame dominant in the two localities on the northernfront. In subsequent years, the parasitoids establishedtheir geographical niches, withE. dispersabeingmore abundant (up to 89%) in the coastal southbellow latitude 7°300N andE. guadeloupae(up to84%) in the north between latitudes 7°300and10°300N. We conclude that the gradual replacementobserved over ten years and over 500 km has to dowith longitudinal shifts in the length and severity ofthe dry season and the higher susceptibility to theseconditions byE. dispersa.